Dental student’s perception to Aesthetic Component of IOTN and demand for orthodontic treatment - Wees Kaolinni; Thalca Hamid; Ervina R. Winoto (Dental Journal (Majalah Kedokteran Gigi), 2013)
Background: The aims of orthodontic treatment are to achieve the best interdigitation in centric occlusion in relation with good facial aesthetic and to get a pleasant dento-facial looked with good function as well. Nowadays, people who are seeking orthodontic treatment to fulfill those need come to orthodontist, mostly for aesthetic reason, for good teeth arrangement that will be more aesthetically favorable. However, not all people with malocclusion seek the orthodontic treatment due to the fact, they do not realize that they have orthodontic problem. On the other hand, some other feel they need orthodontic treatment but they can not afford it. Purpose: To determine the knowledge of malocclusion and demand for orthodontic treatment in related to Aesthetic Component (AC) IOTN. Methods: The samples were 107 college students of Faculty of Dentistry Airlangga University divided into two as 1st and 7th semester group. Both of the groups were given questionnaire about their knowledge of malocclusion and demand of orthodontic treatment. Then, they were asked to examine themselves using AC IOTN, then researcher and orthodontist examine them. Results: There was a significant difference on knowledge of malocclusion between both groups, no significant difference on demand of orthodontic treatment between both groups, and no correlation between demand and AC IOTN in both groups. There was a significant difference in AC IOTN score examined by respondent, researcher and orthodontist. Conclusion: Knowledge of malocclusion was not the only factor that determines demand of orthodontic treatment.Latar belakang: Tujuan perawatan ortodonti adalah untuk mendapatkan hubungan interdigitasi yang baik berhubungan dengan penampilan estetik wajah untuk mendapatkan fungsi dan penampilan dento-fasial yang baik. Saat ini, banyak orang mencari perawatan ortodonti untuk memenuhi kebutuhan fungsi dan penampilan. Tujuannya adalah susunan gigi yang rata yang lebih dapat diterima secara estetik. Namun, tidak semua orang dengan maloklusi mencari perawatan ortodonti, karena sebagian dari mereka tidak menyadari bahwa mereka memiliki masalah ortodonti, sedangkan sebagian lainnya merasa mereka membutuhkan perawatan ortodonti tetapi tidak bisa membiayainya. Tujuan: Mengetahui hubungan pengetahuan maloklusi dan demand perawatan ortodonti dengan Aesthetic Component (AC) IOTN. Metode: Sampel adalah 107 mahasiswa Fakultas Kedokteran Gigi Universitas Airlangga yang dibagi ke dalam 2 kelompok, semester 1 dan semester 7. Kedua kelompok kemudian diberi kuesioner tentang pengetahuan maloklusi dan demand perawatan ortodonti. Kemudian responden diminta untuk menilai diri mereka sendiri menggunakan AC IOTN, setelah itu responden dinilai peneliti dan ortodontis. Hasil: Terdapat perbedaan pengetahuan maloklusi yang signifikan antara kedua kelompok, tidak ada perbedaan demand perawatan ortodonti yang signifikan pada kedua kelompok, tidak ada hubungan antara demand dan AC IOTN pada kedua kelompok. Ada perbedaan yang signifikan pada skor AC IOTN yang diperiksa oleh responden, peneliti dan ortodontis. Simpulan: Pengetahuan maloklusi bukan satu-satunya faktor yang mempengaruhi demand perawatan ortodonti.